KEKACAUAN TINGKAT TUTUR BAHASA JAWA DI LINGKUNNGAN KABUPATEN KEBUMEN JAWA TENGAH - Romelah Romelah (Center of Language and Cultural Studies, 2016)
The purpose of this study was to describe the shape and factors causing environmental unstructured speech level in Kebumen. This study used a qualitative descriptive study. Data of this study were verbal utterances using Javanese uttered by teenagers and adults in Puring District, Kebumen regency, Central Java. The results showed that the shape of the chaos of speech level includes: (a) the form of higher manners (krama inggil) to polite manners (ngoko alus), (b) the form of polite manners (ngoko alus) to higher manners (krama inggil) and (c) to form higher polite manners (ngoko inggil). The unstructured speech levels occur as a result of: (1) lack of knowledge/ understanding of the use poliness patterns of Javanese, (2) direct contact among migrants from Yogyakarta and Solo cities of the native politness Javanese originate, (3) low education level, (4) low frequency of speaking Javanese using polite pattersn, and (5) lack of mastery of vocabulary and speech level in polite manners of Javanese to teach younger generations.